Bryostatin-1: a promising compound for neurological disorders - Tian, Zhen; Lu, Xin-Tong; Jiang, Xun; Tian, Jiao (Frontiers in Pharmacology, 2023)
The central nervous system (CNS) is the most complex system in human body, and there is often a lack of effective treatment strategies for the disorders related with CNS. Natural compounds with multiple pharmacological activities may offer better options because they have broad cellular targets and potentially produce synergic and integrative effects. Bryostatin-1 is one of such promising compounds, a macrolide separated from marine invertebrates. Bryostatin-1 has been shown to produce various biological activities through binding with protein kinase C (PKC). In this review, we mainly summarize the pharmacological effects of bryostatin-1 in the treatment of multiple neurological diseases in preclinical studies and clinical trials. Bryostatin-1 is shown to have great therapeutic potential for Alzheimer’s disease, multiple sclerosis, fragile X syndrome, stroke, traumatic brain injury, and depression. It exhibits significant rescuing effects on the deficits of spatial learning, cognitive function, memory and other neurological functions caused by diseases, producing good neuroprotective effects. The promising neuropharmacological activities of bryostatin-1 suggest that it is a potential candidate for the treatment of related neurological disorders although there are still some issues needed to be addressed before its application in clinic.